2020
DOI: 10.1002/wsb.1135
|View full text |Cite
|
Sign up to set email alerts
|

Nest‐Box Use by Wood Ducks and Black‐Bellied Whistling Ducks in Coastal South Carolina

Abstract: We surveyed nest-structure use by sympatric nesting wood ducks (Aix sponsa) and black-bellied whistling ducks (Dendrocygna autumnalis) across coastal South Carolina, USA, in 2016-2017. Of 718 nest boxes surveyed cumulatively in 2016 and 2017, 61% were used by wood ducks and 15% by black-bellied whistling ducks. Lower nest-box use by whistling ducks was related to recent arrivals and breeding by the species in South Carolina. Nest-box use by wood ducks was 6% greater for every 1,000-cm 3 decrease from the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, as facultative cavity-nesters, Whistling-Ducks have the potential to interact and compete for nest sites with other cavity nesting species, such as the Wood Duck (Aix sponsa). Croft et al (2020) identified substantial niche overlap in both nest box preferences and timing of nesting in South Carolina, where Wood Ducks nested January to July and Journal of Field Ornithology 93(4): 8 https://journal.afonet.org/vol93/iss4/art8/ Whistling-Ducks nested May to September. Given the temporal overlap in nest box use (Croft et al 2020) and that both species are conspecific brood parasites (McCamant and Bolen 1979, Semel et al 1988, James 2000, there is potential for interspecific brood parasitism (IBP) to occur.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, as facultative cavity-nesters, Whistling-Ducks have the potential to interact and compete for nest sites with other cavity nesting species, such as the Wood Duck (Aix sponsa). Croft et al (2020) identified substantial niche overlap in both nest box preferences and timing of nesting in South Carolina, where Wood Ducks nested January to July and Journal of Field Ornithology 93(4): 8 https://journal.afonet.org/vol93/iss4/art8/ Whistling-Ducks nested May to September. Given the temporal overlap in nest box use (Croft et al 2020) and that both species are conspecific brood parasites (McCamant and Bolen 1979, Semel et al 1988, James 2000, there is potential for interspecific brood parasitism (IBP) to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Croft et al (2020) identified substantial niche overlap in both nest box preferences and timing of nesting in South Carolina, where Wood Ducks nested January to July and Journal of Field Ornithology 93(4): 8 https://journal.afonet.org/vol93/iss4/art8/ Whistling-Ducks nested May to September. Given the temporal overlap in nest box use (Croft et al 2020) and that both species are conspecific brood parasites (McCamant and Bolen 1979, Semel et al 1988, James 2000, there is potential for interspecific brood parasitism (IBP) to occur. A single instance of Whistling-Ducks parasitizing Wood Duck nests has been documented in the literature based on two mixed clutches that were incubated by Wood Ducks (Bolen and Cain 1968); there are no publications that document Wood Ducks laying parasitic eggs in Whistling-Duck nests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BBWD are unusual among ducks in that both sexes incubate the nest, and they are facultative secondary cavity-nesters, with nests documented in natural cavities, manmade nest boxes, and on the ground [6][7][8] . As predominately cavity nesters, the expansion of BBWD into the core breeding range of Wood Ducks (Aix sponsa; hereafter, WODU) is potentially of management concern for myriad reasons, including competition for nest sites [9] in areas where breeding phenology of both species overlaps [4,10] . In addition, both conspeci c [11][12][13] and interspeci c [4,14,15] nest parasitism has been documented in BBWD, including parasitism of WODU nests [4] , which has the potential to negatively affect WODU reproductive success by increasing nest abandonment and decreasing egg hatchability [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…As noted, initial efforts to aid a species are rarely perfect. Wood duck boxes are a long-term success but are still being improved after nearly 100 years (Croft, 2018); management gets more complex over time. We see use of boxes as an opportunity to help bats not "a risk to be mitigated by policy.…”
mentioning
confidence: 99%